Novel genetic markers for tracking pH-responsive genes in Pinus sylvestris (L.) - Höhn, Maria; Tóth, Endre György; Major, Enikő Ibolya; Sisa, János; Kovács, Zsófia; Köbölkuti, Zoltán Attila (Frontiers in Ecology and Evolution, 2025)
In ecosystems dominated by acidic soils, species are forced to adapt to unfavorable and stressful substrate conditions and have evolved various strategies. These include a range of physiological and chemical mechanisms and signaling pathways that trigger molecular responses, which has led, in turn, to structural and functional changes in responsive genes. As a result of these adaptations, molecular approaches have enabled considerable progress in explaining the mechanisms and detection of genes responsible for acidic pH tolerance. The development of gene-specific molecular markers offers more options for the marker-assisted detection of substrate-specific populations. Scots pine (Pinus sylvestris L.) is a major forest forming conifer species of Eurasia capable of growing on substrates with different pH values. In this study, based on the annotation of pH-responsive genes, novel SNP markers were identified and tested using Scots pine samples originating from habitats with substrates of varying pH. By testing the primers, 33 markers from 27 gene regions were successfully amplified using PCR. Following the sequencing of the PCR products, gene regions were analyzed, focusing specifically on polymorphic sites and synonymous/non-synonymous SNPs. From a total of 15426 sites, it was possible to identify 8 synonymous and 5 non-synonymous SNPs. The genetic variation revealed by the newly designed markers, affecting species’ soil pH tolerance help to identify individuals adapted to divergent soil types. In such cases, the markers may serve as valuable genetic tools for studies of adaptive genetic variation in Scots pine, a species used in both reforestation and forest plantations.